Influence of implant diameter on implant survival rate and clinical outcomes in the posterior area: a systematic review and meta-analysis - Paolo Pesce; Massimo Del Fabbro; Laura Modenese; Stefano Sandron; Luca Francetti; Gaetano Isola; Luigi Canullo; Maria Menini (BMC, 2023)
Abstract Objective The aim of the present systematic review was to test the hypothesis that the diameter of implants inserted in the posterior area affects implant survival rate, prosthetic survival rate and peri-implant parameters (bleeding on probing (BoP), marginal bone loss (MBL), pocket probing depth (PPD)). Materials and methods An electronic search of studies published until December 2021 was done on three databases (Pubmed, Scopus, Cochrane) independently by two authors. Clinical trials comparing implant survival rate, BoP, MBL and PPD among narrow diameter implants (NDI: ≥ 3.0 mm to < 3.75 mm) and regular diameter implants (RDI ≥ 3.75 mm to < 5 mm) were included. Data were independently extracted by two reviewers. Risk of bias was evaluated according to the Cochrane risk-of-bias tool for randomized studies and to the Joanna Briggs Institute Critical Appraisal tools for non-randomized ones. A pair-wise meta-analysis was conducted on the included studies. Results Seven articles were included out of the 4291 identified from the digital research. Overall, a total of 939 implants were inserted (319 NDI, 620 RDI). Only one study was judged at serious risk of bias. No statistically significant difference was found in implant survival rate (risk ratio 1.01 (95% CI [0.98 to 1.04], P = 0.67)) while the difference was significant for BoP (mean difference 2.89 (95% CI [0.30 to 5.48] mm, P = 0.03)) with higher values for NDI. Higher MBL was identified among regular diameter implants (mean difference -0.15 mm (95% CI [-0.32 to 0.01 mm], P = 0.07). No statistically significant differences were identified for prosthetic survival and PPD. Conclusions No differences were found in implant survival rate between narrow and regular implants. A higher BoP was identified among narrow implants, but there was no higher bone loss. It is not possible to draw definitive conclusions about the use of narrow-diameter implants in the posterior region.